A cross-chain enabled day-ahead collaborative power-carbon-TGC market. (1st November 2022) - Wang, Yun; Xie, Haipeng; Sun, Xiaotian; Tang, Lingfeng; Bie, Zhaohong
Abstract: The contradiction between the independent operation and inner connection of the power market, carbon market and TGC market have become the primary challenge towards developing renewable energy and low-carbon technologies. This paper proposes a day-ahead collaborative power-carbon-TCG market framework and its implementation methodology based on the cross-chain technology to cope with the challenge. The daily collaborative market is designed to operate sequentially to reflect the time attribute of carbon emission and TGC production. Penalty factors are introduced in the power market to indicate the inter-market influences from the carbon and TGC markets. Furthermore, cross-chain technologies are leveraged to form a unified framework for the coordination of the three markets, and the chain structures of each market are redesigned to fit into the unified framework. The conclusion is drawn from the case studies on the modified IEEE-30 bus system. The results indicate that the total carbon emission of the system is reduced under the collaborative market framework. The market shares and profits of low-emission and renewable units increase vastly, benefiting low-carbon and renewable energy companies in the long term. Highlights: Established a day-ahead collaborative market framework for power, carbon and tradable green certificate (TGC). Introduced penalty factors in the market clearance to indicate inter-market influences. Developed a heterogeneous multi-chain structure for the market framework. Redesigned the blockchain structures for each market for practical use.